Investing in Women, Inspiring Inclusion, Strengthening Climate Resilience - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2024)
In line with the theme for International Women's Day 2024, "Invest in Women, Accelerate Progress," Researchers from ICARDA and Western University, Canada, under the auspices of the CGIAR Initiative, HER+, which aims to achieve climate resilience through gender equality and social inclusion in Global South food systems, take stock of public policies and local governance mechanisms that improve women's participation in climate governance and increase women's resilience in the hard-hit agricultural regions of the Global South.